The Role of Social Class in the Use of Gender-Inclusive Language: An Analysis of Polish and German Job Titles - Lea Hodel; Magdalena Formanowicz; Agnieszka Pietraszkiewicz; Sabine Sczesny (Social Psychological Bulletin)
Past research has found that gender-inclusive language is more commonly used in egalitarian cultures. People in middle-class communities not only endorse more egalitarian values but also more strongly believe that social change is possible than people in working-class communities. As such, there may be a higher demand for and, thus, use of gender-inclusive language in middle-class professions than for working class professions. Two studies investigated the use of feminine and gender-inclusive job titles for working vs. middle class professions in two grammatical gender languages, namely feminine job titles in Polish corpus texts (Study 1) and gender-inclusive job titles in Swiss German job advertisements (Study 2). Results showed that feminine and gender-inclusive job titles were indeed more often used for middle- than for working-class professions in both countries. These findings document the need to take social class into account in future language research as well as in the implementation of language reforms.